Adaptive Consensus Mechanisms for Dynamic Blockchain Environments (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2025)
Blockchain networks do not stand still. Validator counts change as members join and leave consortia. Transaction loads spike during market events and drop at weekends. Network conditions shift as infrastructure is upgraded, partitions occur, and adversaries come and go. Yet the consensus mechanism at the heart of most blockchains is fixed at deployment -- tuned for a single operating point and left there, performing well in one regime and poorly in others. Adaptive consensus mechanisms respond to changing conditions by adjusting their own parameters -- block size, timeout durations, leader rotation frequency, sampling parameters, and even the underlying protocol family -- in real time. We present the Adaptive Consensus Framework (ACF), which designs and evaluates three adaptive strategies: parameter-adaptive consensus (adjusting protocol parameters within a fixed protocol), mode-switching consensus (switching between protocol families based on conditions), and ML-driven consensus tuning (using reinforcement learning to optimise consensus parameters online). We test all three on Hyperledger Fabric 2.5 and a custom Tendermint fork under six dynamic scenarios including load spikes, validator churn, and Byzantine fault injection. Our Adaptive Quality Score (AQS) shows that ML-driven tuning achieves the highest sustained throughput (0.916 AQS) but parameter-adaptive consensus offers the best stability-to-complexity ratio. Mode-switching delivers the widest operating envelope at the cost of transition overhead averaging 4.2 seconds.